Impact of shift duration on alertness among air‐medical emergency care clinician shift workers. Issue 4 (7th February 2019) - Patterson, P. Daniel; Weaver, Matthew D.; Markosyan, Mark A.; Moore, Charity G.; Guyette, Frank X.; Doman, Jack M.; Sequeira, Denisse J.; Werman, Howard A.; Swanson, Doug; Hostler, David; Lynch, Joshua; Templin, Megan A.; et al.
Abstract : Background: Greater than half of Emergency Medical Services (EMS) shift workers report fatigue at work and most work long duration shifts. We sought to compare the alertness level of EMS shift workers by shift duration. Methods: We used a multi‐site, 14‐day prospective observational cohort study design of EMS clinician shift workers at four air‐medical EMS organizations. The primary outcome was behavioral alertness as measured by psychomotor vigilance tests (PVT) at the start and end of shifts. We stratified shifts by duration (< 24 h and 24 h), night versus day, and examined the impact of intra‐shift napping on PVT performance. Results: One hundred and twelve individuals participated. The distribution of shifts <24 h and 24 h with complete data were 54% and 46%, respectively. We detected no differences in PVT performance measures stratified by shift duration ( P > 0.05). Performance for selected PVT measures (lapses and false starts) was worse on night shifts compared to day shifts ( P < 0.05). Performance also worsened with decreasing time between waking from a nap and the end of shift PVT assessment. Conclusions: Deficits in performance in the air‐medical setting may be greatest during night shifts and proximal to waking from an intra‐shift nap. Future research should examine alertness and performance throughout air‐medical shifts, as well as investigate the timing and duration of intra‐shift naps on outcomes.